A pilot study: pledge your teeth! The willingness of dental students to donate their teeth - Ishak, Hayati; Mohamed Zohdi, Noorharliana; Mohd Zairi, Masyitah; Zaharudin, Sajidah (IIUM Journal of Orofacial and Health Sciences, 2020)
Extracted human teeth is the preferred choice for preclinical training as it simulates the clinical scenario as compared to artificial teeth. However, the increase in the number of dental undergraduates might cause an imbalance in the demand and supply of extracted human teeth. Not only that, extracted human teeth are also needed by researchers for the development of dentistry (e.g. dental pulp stem cells research). This study aimed to evaluate the socio-demographic and preclinical training factors associated with the willingness to donate teeth among dental students of a selected university in Malaysia. The results of this study show that the majority of students were willing to donate their teeth after extraction for educational purposes, followed by keeping their tooth, leaving it behind as clinical waste and donating it to research. Further research is recommended to determine the willingness of the community or public to donate their teeth to meet the demand for dental schools and researchers in Malaysia.